Integrating generative AI in higher education for lifelong learning - Mozaffar Alam Chowdhury; Toong Hai Sam; Md. Sohel Rana; Khan Sarfaraz Ali; Whee Yen Wong; Hasanuzzaman Tushar (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study investigates the impact of generative artificial intelligence (GenAI) on learning outcomes (LO) and lifelong skills (LLS) within higher education, emphasizing ethical considerations. Employing a quantitative approach, data was collected from 180 students via a questionnaire, examining their AI usage in education. Structural equation modeling (SEM) using SmartPLS 4.1.0.9 was used to analyze the relationship between GenAI use, LO, and LLS. Findings reveal that GenAI can enhance LO, personalize learning experiences, and contribute to developing crucial LLS. However, the study highlights the importance of ethical guidelines to prevent academic dishonesty. This research contributes to the existing literature by exploring the link between GenAI use, LO, and the development of LLS. Practically, it demonstrates that ethical GenAI use promotes both LO and LLS among higher education students, aligning with the sustainable development goals (SDGs) of inclusive and equitable quality education and lifelong learning opportunities.